Popularization of Music Education on the Example of Musical and Theatrical Project Dirty Dancing - Nuhanović, Sanja; Ferović-Fazlić, Alma (''Music in Society'' The Collection of Papers, 2020)
The paper deals with reflections on the reasons to the decreased interest of students in formal music education, and opportunities to improve music education system in terms of its popularization. Learning period students spend in order to musically develop and educate themselves should not be a burden, but enjoyment, and flexibility of curriculum in music schools should deliver it. One way of enriching music education could be by including students in various projects, which can be achieved through cooperation with artists outside the home institution, whether amateurs or professionals, but also to connect with similar arts, if the project requires it. In addition to the learning process, it is important to think of the other, no less important, educational component, that would encourage students to think further and, if they continue with education, how to become a performer on stage, and thus have the opportunity to travel, to collaborate with other artists and make new friends. As an example of a successful cooperation on the international level we are presenting a musical and theatrical project Dirty Dancing, which got together a large number of amateur and professional artists, whose teamwork led to the successful live performance and project realization.